Antiretroviral therapy in primary HIV infection. (May 2013) - Powderly, William G
Evaluation of: SPARTAC Trial Investigators, Fidler S, Porter K et al. Short-course antiretroviral therapy in primary HIV infection. N. Engl. J. Med. 368, 207–217 (2013). The timing of antiretroviral therapy (ART) in patients who present with primary HIV infection is uncertain. This paper compared three strategies: ART for 48 weeks; ART for 12 weeks; or no therapy in 366 patients with primary HIV infection. They showed that 48 weeks of ART significantly reduced the risk of needing definitive therapy (after a median follow-up of 4.2 years). However, the median delay in needing to start definitive therapy (61 weeks) is not significantly greater than the amount of treatment given (48 weeks) to achieve this result, suggesting that the clinical benefit of immediate ART in primary HIV infection is not yet clear